A new fossil mantis fly (Insecta: Neuroptera: Mantispidae) from the Lower Cretaceous of the Democratic People's Republic of Korea. (July 2022) - So, Kwang-Sik; Won, Chol-Guk
Abstract: A new fossil mantis fly, Sinuijumantispa ryonsangiensis gen. et sp. nov. is described from the third member of the Lower Cretaceous (Barremian-Aptian) Sinuiju Formation of Ryonsang-dong in Sinuiju City, North Phyongan Province, DPRK. It is assigned to the stem-group of the subfamily Drepanicinae (Insecta: Neuroptera; Mantispidae). The holotype exhibits profemur with one major-, sub-basal spine, more than five spines larger than remaining spines along the ventral face; costal space most dilated basally; Sc meets R1 in region of pterostigma; Sc and R parallel for most of length; costal space of hind wing gradually narrow towards wing base, with simple and straight veinlets. This well preserved specimen enhances our understanding of the palaeobiogeography of Mantispidae, broadens the diversity of this family, and provides morphological characters for future phylogenetic studies of Mantispidae. Highlights: Sinuijumantispa ryonsangiensi s gen. et sp. nov. from the Sinuiju Formation was firstly discovered. It is the first fossil drepanicine genus in the Jehol biota. It belongs to family Mantispidae (Insecta: Neuroptera). This description increases the diversity of Mantispidae from the Lower Cretaceous.